2020
DOI: 10.1097/brs.0000000000003846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Surgical Systems for Treatment of Early-onset Scoliosis in the Context of Release of Titanium Ions

Abstract: Study Design. Case–control study. Objective. The aim of the study was to compare growth-friendly systems: traditional growing rod, guided growth systems (GGS), and vertical expandable prosthetic titanium rib in the context of titanium release. Summary of Background Data. The problem of scoliosis affects even up to 3% of the population, and ca. 0.1% of patients need surgical treatment. Surgical treatment carries the risk of a long-term presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…However, problems with the loss of fixation and failure of the implants in some cases persist[ 10 , 47 ]. Some authors have pointed out an additional problem connected with metal debris which appears in the serum and surrounding tissues[ 52 ]. Although it does not directly affect the outcome of the treatment, it is worth considering this occurrence as undesirable/a complication.…”
Section: Discussionmentioning
confidence: 99%
“…However, problems with the loss of fixation and failure of the implants in some cases persist[ 10 , 47 ]. Some authors have pointed out an additional problem connected with metal debris which appears in the serum and surrounding tissues[ 52 ]. Although it does not directly affect the outcome of the treatment, it is worth considering this occurrence as undesirable/a complication.…”
Section: Discussionmentioning
confidence: 99%
“…They also carry the risk of many problems and complications [1,2]. The emerging surgical techniques and new implants have not yet brought about considerable change in the concept of the procedure, and the exposure of a substantial part of the spine is necessary, which certainly contributes to post-operative pain [3,4]. Effective pain management after posterior spinal fusion, in paediatric patients, is an essential part of surgical treatment for increasing patient's comfort, allowing quicker convalescence.…”
Section: Introductionmentioning
confidence: 99%
“…The primary composition of these implants is titanium, which has previously been recognized as an inert and biocompatible substance 4 . However, recent studies have demonstrated that titanium can be gradually released into local tissues from mechanical wear, such as friction and bending, in ionized and nanoparticle forms that are absorbed in the bloodstream and transported to other organ systems 5,6 . There have been a number of studies that have reported significant metallosis and wear debris in the soft tissues of patients with growth-friendly implants (GFI) 7–11 .…”
mentioning
confidence: 99%
“…4 However, recent studies have demonstrated that titanium can be gradually released into local tissues from mechanical wear, such as friction and bending, in ionized and nanoparticle forms that are absorbed in the bloodstream and transported to other organ systems. 5,6 There have been a number of studies that have reported significant metallosis and wear debris in the soft tissues of patients with growth-friendly implants (GFI). [7][8][9][10][11] As a result of this local debris deposition, macrophages, and cytokines are recruited to the area, initiating an inflammatory response that can possibly lead to pseudoarthrosis, osteolysis, and late postoperative surgical site infection.…”
mentioning
confidence: 99%